Introduction to music therapy practice - Heiderscheit, Annie; Jackson, Nancy (Nancy A.) (Barcelona Publishers, 2018)
An overview of music therapy clinical practice in the 21st century, structured around the ways music therapists engage clients in music experiences - re-creating, composing, improvising and active listening. The text includes forty-eight case illustrations from twenty-nine clinicians practicing with diverse client populations. These cases demonstrate how the music therapist adapts the method to meet the unique needs and interests of clients. The benefits of these methods are outlined, and representative research is provided to support clinical applications. Ten context examples written by ten.